Aspartate Aminotransferase Purification from Dyslipidaemia Patients and Study of The Inhibitory Potently Effect Zn-Schiff Base Complex - Al.Faraji, Saif Mahmood (American Journal of Bioscience and Clinical Integrity, 2025)
Introduction: Hyperlipidemia refers to abnormal Elevated lipid levels and/or lipoproteins present in the bloodstream. AST is an enzyme localized in both the mitochondrial and cytoplasmic , serves as a recognized biomarker for cellular damage in the liver, heart muscle, and skeletal muscle. Materials and methods: A fifty Specimens of blood were collected through the laboratories affiliated with Baghdad Hospital for the period (October 2024 to February 2025). Determination of AST activity and total protein concentration by a simple colorimetric assay kits . Isolation and purifications of the AST enzyme from (10) ml fresh serum of human by steps. And prepared a tetrahedral Zn(II) complex with the ligand (E))-5--methoxy-2ـــ[(oــtolylimino)methyl]phenol and spectroscopic characterization Results: There was A marked and An increase that was statistically significant at (P < 0.001) in triglyceride concentration, AST activity in the patients’ group showed no significant change (P > 0.05) comparing to control groups. The purified AST DEAE-cellulose ion exchange chromatography peak showed particular activity 1.3 U/ mg with 3.34 folds of purification, suggesting that an enzyme represented during this peak is suitable for additional purification. The activity of AST purified by Gel filtration chromatography reached 12.2 U/L . Moreover, An enhancement in AST specific activity was recorded, reaching 2.25 ـU/mg by (5.78) folds. And enzyme yields 18.4 %. A linear correlation was observed Demonstrating the enzyme’s Km and Vmax values as (172.729mM and 31.156 IU/L) for AST. showed the activity were decreased with Pd complex. Also, km and Vmax were decreased with novel Zn-Schiff base complex comparing without complex. Conclusions : The synthesized novel Zn-Schiff base showed an inhibitory effect on AST activity purified from the serum of dyslipidemia patients with low Km and V max, which indicates that the inhibition type is uncompetitive.